[Group in Swimwear at Landmanns Laugar] - Streng, Evelyn Fiedler (1975)
Photograph of men in swimwear at Landmanns Laugar in Iceland. A rock covered path cuts through a grassy field surrounded by hills of green grass and black, jagged rocks. The group of three people wear black, red, and white swim shorts and boots as they walk along the path toward the rocky hill. A long, metal pipe runs parallel to the path to the left.